2019
DOI: 10.1371/journal.pone.0210550
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic analysis of human influenza A and B viruses in Myanmar, 2010–2015

Abstract: We investigated the circulation patterns of human influenza A and B viruses in Myanmar between 2010 and 2015 by analyzing full HA genes. Upper respiratory tract specimens were collected from patients with symptoms of influenza-like illness. A total of 2,860 respiratory samples were screened by influenza rapid diagnostic test, of which 1,577 (55.1%) and 810 (28.3%) were positive for influenza A and B, respectively. Of the 1,010 specimens that were positive for virus isolation, 370 (36.6%) were A(H1N1)pdm09, 327… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Myanmar has a tropical monsoon climate with three seasons: winter (November-February), summer (March-Mid May), and rainy (Mid May-October) seasons, based on the analysis of pressure, rainfall, and temperature [26]. The study showed that the circulation of influenza viruses peaked in July, which is consistent with previous studies showing that the influenza season in Myanmar peaked in July or August, during the rainy season [6][7][8]. This observation is also similar to the national surveillance data reported to the regional and global influenza surveillance platform (FluNET), which showed that the regional influenza outbreak started during the rainy season from July (week 29) to September (week 36), and influenza virus activity peaked in August with 369 flu-positive cases during the reported weeks 31-35 in 2017 [27].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Myanmar has a tropical monsoon climate with three seasons: winter (November-February), summer (March-Mid May), and rainy (Mid May-October) seasons, based on the analysis of pressure, rainfall, and temperature [26]. The study showed that the circulation of influenza viruses peaked in July, which is consistent with previous studies showing that the influenza season in Myanmar peaked in July or August, during the rainy season [6][7][8]. This observation is also similar to the national surveillance data reported to the regional and global influenza surveillance platform (FluNET), which showed that the regional influenza outbreak started during the rainy season from July (week 29) to September (week 36), and influenza virus activity peaked in August with 369 flu-positive cases during the reported weeks 31-35 in 2017 [27].…”
Section: Discussionsupporting
confidence: 88%
“…Since then, it has been co-circulating with other seasonal influenza viruses in the country. Previously, we reported the epidemiology and genetic characterization of influenza virus A and B circulating in Myanmar [6,7] and characterized the drug-susceptibility of seasonal and pandemic influenza A(H1N1) viruses in Myanmar in 2008 and 2009 [8]. Only 16 sporadic cases of A(H1N1)pdm09 were detected in 2009, and genotyping of these viruses showed no mutations in neuraminidase (NA), which indicated susceptibility to oseltamivir [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the antigenic and genetic evolutionary dynamics of the virus have resulted in the emergence of several subtypes and clades which have been quit diverse across the region. 35 For instance, there are reports of the emergence of the new clade 1.1.2 and 2.3.2.1 reassortant A(H5N1) virus and clade 3c.2a and 3c.3a A(H3N2) virus between 2012-2015. 15,17 Within this same period, other new reassortant clades were detected for influenza A (H3N2) and B viruses in Laos PDR, Taiwan, Malaysia, Myanmar, Thailand, Japan, China and Vietnam.…”
Section: Epidemiology Seasonal Patterns and Viral Types/subtypesmentioning
confidence: 99%
“…15,17 Within this same period, other new reassortant clades were detected for influenza A (H3N2) and B viruses in Laos PDR, Taiwan, Malaysia, Myanmar, Thailand, Japan, China and Vietnam. 35,36 The finding implies that there is the need for a sustained approach in the regions periodic update of information provided to the WHO global influenza surveillance response (GISRS) system which is a mechanism designed by the WHO for deciding the antigenic and genetic composition of influenza vaccines used in the different hemispheric zones. 5,21,27 Currently, WHO has approved the use of trivalent or quadrivalent vaccines that protect against the three predominant strains which are; influenza A (H1N1), A (H3N2), and B viruses in most countries.…”
Section: Epidemiology Seasonal Patterns and Viral Types/subtypesmentioning
confidence: 99%
“…For a long time, much effort has been done on Flu A virus, whereas Flu B virus was relatively less investigated, resulting in poor lineage matches with recommended in uenza vaccine strains and the control options require further improvement (Htwe et al 2019;Noh et al 2018). HI tests measure the presence of speci c antibodies of IgG in sera that inhibit virus-mediated agglutination of erythrocytes (Rowe et al 1999).…”
Section: Introductionmentioning
confidence: 99%